Recurrent intragenic rearrangements of EGFR and BRAF in soft tissue tumors of infants - Wegert, Jenny; Jones, David T. W.; Kölsche, Christian; Pfister, Stefan (Nature Communications, 2018)
Soft tissue tumors of infancy encompass an overlapping spectrum of diseases that pose unique diagnostic and clinical challenges. We studied genomes and transcriptomes of cryptogenic congenital mesoblastic nephroma (CMN), and extended our findings to five anatomically or histologically related soft tissue tumors: infantile fibrosarcoma (IFS), nephroblastomatosis, Wilms tumor, malignant rhabdoid tumor, and clear cell sarcoma of the kidney. A key finding is recurrent mutation of EGFR in CMN by internal tandem duplication of the kinase domain, thus delineating CMN from other childhood renal tumors. Furthermore, we identify BRAF intragenic rearrangements in CMN and IFS. Collectively these findings reveal novel diagnostic markers and therapeutic strategies and highlight a prominent role of isolated intragenic rearrangements as drivers of infant tumors.